Logic circuit designing using optically controlled MESFET - Bandhawakar G.; Pal B.B. (My University, 2025)
Since their introduction in 1970's GaAs MESFETs have shown their outstanding performance in various high frequency applications, especially in upper microwave and millimeter range. After a decade in 80's research efforts in GaAs OPFET development came in to focus and gained rapid foothold in high-speed arena. The most attractive feature for development of GaAs MESFET IC's under optically controlled condition is to persue the highest possible switching speed and the other is to realize very low power dissipation, so as to make large-scale integration possible. These devices exhibit multifunction such as optical amplification, bistability and switching. Optoelectronic integrated circuits (OEICs) are of great interest and widely applied for high speed integrated circuits (IC's). Such as optical fiber communication systems, telecommunication and computer industries. In present paper we have presented a DCFL (Direct Coupled Field Effect Transistor Logic) using OPFET's. Several set of analytical equations have been derived, which relates the inverter parameter to the parameter of switching transistor and saturated load. For both the switching transistor and saturated load, MESFETs have been used and gate of switching transistor has been illuminated optically, thus a photovoltage (Vop) develop at gate. Furthermore, the photogenerated electrons in the depletion and channel region contribute to excess current which is added to dark channel current to give the total channel current. All the inverter parameters such as the load saturation current, the switching transistor threshold voltage and inverter turn - on and off time show better performance under illumination rather than under dark condition. This device using OPFET can be a useful tool in the areas of optical communication and can be used as switches and/or logic gates in OEICs. © 2002 SPIE.